P.038 A case report of an interesting paraneoplastic voltage-gated channelopathy. (17th June 2016) - Richard, A; Legault, C; de Villers-Sidani, E; Gendron, D
Abstract : Background: Morvan syndrome is an autoimmune paraneoplastic disorder affecting of voltage-gated potassium channels, most commonly the CASPR-2 subunit. The disorder is primarily characterized by hyperexcitability of both the central and peripheral nervous system accompanied by autonomic dysfunction. Clinically, the syndrome manifests as confusion, hallucinations, insomnia, hyperhidrosis, orthostatic hypotension, and muscle cramps with myoclonus. Methods: Patient chart, imaging, electrophysiology, and laboratory findings were reviewed from the time of MS diagnosis and through the course of treatment until symptom resolution. Results: Here we report a case of Morvan Syndrome in a 56 year old male with a previous history of thymic squamous carcinoma accompanied by paraneoplastic myasthenia gravis and myositis. His clinical presentation was notable for subacute onset of muscle cramping, insomnia, which progressed to also include visual and auditory hallucinations. He also had notable dysautonomic symptoms including orthostatic blood pressure changes, sialorrhea, and hyperhidrosis. The diagnosis was confirmed with a positive serum assay for antibodies against the CASPR-2 subunit of voltage-gated potassium channels. Conclusions: This case is notable because to our knowledge it one of the first to document a voltage-gated channelopathy in association with previous thymic cancer (and not thymoma). Moreover, this is a patient presenting with two other other autoimmune syndromes, i.e. myasthenia gravis and myositis.